2014
DOI: 10.1158/0008-5472.can-14-0772-t
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 Mutations Alter Citric Acid Cycle Metabolism and Increase Dependence on Oxidative Mitochondrial Metabolism

Abstract: Oncogenic mutations in isocitrate dehydrogenase 1 and 2 (IDH1/2) occur in several types of cancer, but the metabolic consequences of these genetic changes are not fully understood. In this study, we performed 13C metabolic flux analysis on a panel of isogenic cell lines containing heterozygous IDH1/2 mutations. We observed that under hypoxic conditions, IDH1-mutant cells exhibited increased oxidative tricarboxylic acid metabolism along with decreased reductive glutamine metabolism, but not IDH2-mutant cells. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
237
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(267 citation statements)
references
References 50 publications
18
237
1
Order By: Relevance
“…In all, our results suggest that altered oxidative stress response is the most likely downstream element of causing mitochondrial ROS (54). In addition, other Achilles' heels in IDH MT metabolism could be exploited, such as mitochondrial dysfunction (50), increased dependence on glutaminolysis (2,(55)(56)(57)(58)(59) and oxidative phosphorylation (42,43). These vulnerabilities can be pharmacologically targeted via BCL-2 inhibitors, chloroquine, and metformin, respectively.…”
Section: Idhmentioning
confidence: 85%
See 1 more Smart Citation
“…In all, our results suggest that altered oxidative stress response is the most likely downstream element of causing mitochondrial ROS (54). In addition, other Achilles' heels in IDH MT metabolism could be exploited, such as mitochondrial dysfunction (50), increased dependence on glutaminolysis (2,(55)(56)(57)(58)(59) and oxidative phosphorylation (42,43). These vulnerabilities can be pharmacologically targeted via BCL-2 inhibitors, chloroquine, and metformin, respectively.…”
Section: Idhmentioning
confidence: 85%
“…MT cells are sensitized to antidiabetic biguanides such as metformin (42,43), which also depend on oxidative stress to induce cell death (44 …”
Section: Idh1mentioning
confidence: 99%
“…Reductive carboxylation of glutamine-derived α-ketoglutarate is an important survival mechanism in mammalian cells and constitutes a pathway to maintain citrate synthesis and lipogenesis in oxygen-deprived cells (21,22,47,48). In contrast, cells expressing mutant IDH are no longer capable of performing reductive carboxylation and exhibit an increased dependence on oxidative mitochondrial metabolism (49,50). Hence, cells that accumulate D-2HG using an alternative pathway, like ADHFE1, may have a survival advantage under hypoxic conditions because of their continued ability to use reductive carboxylation for acetyl-CoA synthesis.…”
mentioning
confidence: 99%
“…It is important to note that IDH1 mutant gliomas demonstrate improved overall survival compared to their wild‐type counterparts,52 which may well be in some part due to their apparent inability to modify their mitochondrial metabolism in response to hypoxia. Interestingly, IDH2 ‐mutated cells were shown not to exhibit the same alteration in the hypoxia‐mediated mitochondrial metabolic phenotype 117. These data may shed more light on the metabolic differences induced by IDH1 and IDH2 mutations and therefore their different prevalence in glioma—a highly hypoxic type of tumor.…”
Section: Mutations Of Mitochondrial (And Associated) Metabolic Enzymementioning
confidence: 86%
“…Given that the cytosolic pathway has been shown to be important in hypoxic reductive carboxylation for lipogenesis,30, 32, 33, 34 and that gliomas appear to ‘favor’ IDH1 mutations, there may be a requirement for IDH2 wild‐type activity in hypoxic IDH1 mutant gliomas. However, a recent paper also showed that IDH1 ‐mutated cells retained more of their oxidative TCA cycle metabolism than their wild‐type counterparts 117. Under hypoxic conditions, where IDH1 wild‐type cells increased their dependence on reductive carboxylation of glutamine, IDH1 mutant cells increased their use of oxidative decarboxylation, most likely retaining oxidative ATP generation in these conditions.…”
Section: Mutations Of Mitochondrial (And Associated) Metabolic Enzymementioning
confidence: 99%